Prevalence and characterization of heart failure in a population of integrated care users. (14th October 2021) - Gavina, C; Seabra Carvalho, D; Valente, F; Bernardo, F; Santos Araujo, C; Taveira Gomes, T
Abstract: Introduction: Heart failure (HF) is a clinical syndrome caused by structural and functional cardiac abnormalities resulting in impairment of cardiac function, entailing significant morbi-mortality. HF is an age-dependent entity associated with cardiovascular (CV) risk factors such as type 2 diabetes (T2D). Purpose: Estimate the prevalence of HF and its subtypes, and characterize HF in a population of integrated care users. Methods: Non-interventional cross-sectional study performed in healthcare centre that provides primary and secondary care. All adult patients at 31/12/2019 were included. Echocardiographic parameters [left ventricle ejection fraction (LVEF) and evidence of structural heart disease] and elevated level of natriuretic peptides were used to define two HF phenotypes: i) HF with reduced ejection fraction (HFrEF, LVEF ≤40% and either NT-proBNP ≥400pg/mL (≥600pg/mL if atrial fibrillation (AF)/flutter) or BNP ≥100pg/mL (≥125pg/mL if AF/flutter)and ii) HF with non-reduced ejection fraction (HFnrEF), that encompasses both HFpEF (LVEF ≥50% and either NT-proBNP ≥200pg/mL (≥600pg/mL if AF/flutter) or BNP ≥100pg/mL (≥125pg/mL if AF/flutter) in the presence of at least one structural cardiac abnormality) and HF mid-range ejection fraction (HFmEF, LVEF within ]40, 50% [and either NT-proBNP ≥200pg/mL (≥600pg/mL if AF/flutter) or BNP ≥100pg/mL (≥125pg/mL if AF/flutter) in the presence of at least one structural cardiac abnormality). The significance threshold was set at P≤0.001. Results: We analysed 126636 patients with mean age of 52.2 (SD=18.3) years, 57% (N=72290) were female. The prevalence of HF was 2.1% (N=2700). HF patients mean age was 74.0 (SD=12.1) years and 51.6% (N=1394) were female. Regarding HF subtypes, HFpEF accounted for 65.4% (N=1765), 16.1% (N=434) had HFmEF and 16.3% (N=439) had HFrEF. Patients with HFrEF were younger (P<0.001) and had a history of myocardial infarction more frequently (P<0.001) comparing to HFnrEF, with no other significant differences between HF groups. HFrEF patients were more frequently prescribed CV medications than HFnrEF patients, namely antiplatelet agents, ACE inhibitors (55.6% vs 32.7%, P<0.001), beta blockers (79.3 vs 55.8%, P<0.001) and aldosterone receptor antagonists (48.7 vs 8.3%, P<0.001). T2D was present in 44.7% (N=1207) of HF patients. CKD was more frequently present in T2D vs non-T2D HF patients at every stage (P<0.001) as well as stroke, peripheral artery disease and microvascular disease (P<0.001) (Table 1). Conclusions: In this cohort, considering a contemporary definition, HF prevalence was 2.1%; HFrEF accounted for 16.3% of cases, with similar clinical-epidemiological profile previously reported in the literature. Our study revealed a high prevalence of patients with HFpEF (65.4%), raising awareness for the increasing prevalence of this entity in cardiology practice. These results may guide local and national health policies and strategies for HF diagnosis and management. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AstraZeneca, Produtos Farmacêuticos Lda